Evolution of the Plant Reproduction Master Regulators LFY and the MADS Transcription Factors: The Role of Protein Structure in the Evolutionary Development of the Flower - Silva, Catarina S.; Puranik, Sriharsha; Round, Adam; Brennich, Martha; Jourdain, Agnès; Parcy, François; Hugouvieux, Veronique; Zubieta, Chloe (Frontiers in Plant Science, 2016)
Understanding the evolutionary leap from non-flowering (gymnosperms) to flowering (angiosperms) plants and the origin and vast diversification of the floral form has been one of the focuses of plant evolutionary developmental biology. The evolving diversity and increasing complexity of organisms is often due to relatively small changes in genes that direct development. These “developmental control genes” and the transcription factors (TF) they encode, are at the origin of most morphological changes. TFs such as LEAFY (LFY) and the MADS-domain TFs act as central regulators in key developmental processes of plant reproduction including the floral transition in angiosperms and the specification of the male and female organs in both gymnosperms and angiosperms. In addition to advances in genome wide profiling and forward and reverse genetic screening, structural techniques are becoming important tools in unravelling TF function by providing atomic and molecular level information that was lacking in purely genetic approaches. Here we summarise previous structural work and present additional biophysical and biochemical studies of the key master regulators of plant reproduction – LEAFY and the MADS-domain TFs SEPALLATA3 and AGAMOUS. We discuss the impact of structural biology on our understanding of the complex evolutionary process leading to the development of the bisexual flower.